The name Synallaxis whitneyi Pacheco and Gonzaga, 1995, is not a synonym of Synallaxis cinereus Wied, 1831 (Aves: Passeriformes: Furnariidae) - Stopiglia, Renata; Raposo, Marcos A. (Zootaxa, 2006)
Synallaxis whitneyi Pacheco and Gonzaga, 1995, was described from specimens collected in Bahia, Brazil. Some years later, following analysis of the specimens used by Wied (1831) to describe Synallaxis cinereus, Whitney and Pacheco (2001) considered S. whitneyi a junior synonym of S. cinereus because three of the specimens in Wied’s series were identical to those collected in Bahia by Pacheco and Gonzaga (1995). They also designated a lectotype for Synallaxis cinereus. Our analysis of the description of Synallaxis cinereus reveals that Wied was merely providing a new name for Parulus ruficeps Spix, 1824, to avoid problems of homonymy (Wied 1831). The International Code of Zoological Nomenclature is explicit in such cases, stating that if an author proposes a new species-group name as a replacement (nomen novum) for an earlier available one, then the two names are objective synonyms and have the same name-bearing type. Thus, the syntypes of S. cinereus are the specimens previously used by Spix in describing Parulus ruficeps and not those used by Wied (1831) in his description (and subsequently referred to as syntypes in the literature). The lectotype of Synallaxis cinereus proposed by Whitney and Pacheco (2001) is invalid, as it is not a former syntype. Therefore, the correct name for the Bahia Spinetail is Synallaxis whitneyi Pacheco and Gonzaga, 1995.